The persistent consequences of adverse shocks: how the 1970s shaped UK regional inequality - Rice, PG; Venables, AJ (Oxford University Press, 2021)
The economic shocks experienced by the UK economy in the 1970s brought major changes in the spatial distribution of employment rates in the UK. This paper traces the long-run implications of these changes, suggesting that they were highly persistent and to a large extent shape current UK regional disparities. Most of the Local Authority Districts that experienced large negative shocks in the 1970s had high deprivation rates in 2015, and they constitute two-thirds of all districts with the highest deprivation rates. We conclude that neither economic adjustment processes nor policy measures have acted to reverse the effect of negative shocks incurred nearly half a century ago.